Bahasa sastera dan budaya Malaysia-Indonesia - Maslida Yusof; Mohammed Azlan Mis; Yusmilayati Yunos; Mohamad Rodzi Abd. Razak (Penerbit Universiti Kebangsaan Malaysia, 2015)
On aspects of language, literature, and civilization of Indonesian and Malaysian people to create their identities; proceedings of a symposium